The effect of hormonal contraceptive on low birth weight baby delivery in Agronursing Area - Ira Rahmawati; Dini Kurniawati; Yeni Fitria (Nursing and Health Sciences Journal (NHSJ), 2021)
Babies born with low birth weight (LBW) have a high risk and will have an impact on subsequent development. Studies show that the use of hormonal contraceptives can increase the risk of experiencing subjective health complaints than non-hormonal contraceptives. The study is an analytical descriptive study that aims to identify the effect of hormonal contraceptive used on low birth weight baby delivery. The study was conducted in three agricultural hospitals and three public hospitals in the Agriculture area of Besuki Residency. Data analysis of the sample was carried out by quota sampling. Characteristics of respondents were displayed by univariate analysis. The total number of participants in this study were 441 participants. Participants were divided into several data categories such as age, parity, medical history, previous history of preeclampsia, low birth weight babies, contraceptives used, complications of premature rupture of membranes. There two factors, that can predict the low birth weight baby delivery. They are hormonal contraceptives use and premature rupture of membranes. The test results get the hormonal contraceptive used factor to be the strongest factor (OR 19,12). Thus it was concluded "the hormonal contraceptive used factor is an abdominal factor of low birth weight baby delivery with a significance value of 0.000 (p0.05).